P04.07 The molecular evolution of oligodendrogliomas. (9th September 2021) - Padovan, M; Vallentgoed, W; de Heer, I; Lombardi, G; van den Bent, M; French, P
Abstract: BACKGROUND: Oligodendroglioma (OD) is defined by the presence of both IDH1/2 mutation and 1p/19q codeletion. Although prognosis of OD patients is relatively favorable, tumours usually relapse and often evolve to a higher malignancy grade, with some acquiring the treatment induced hypermutated phenotype. To better understand how these tumours evolve in time, we examined the molecular differences between matched primary and recurrent ODs. MATERIAL AND METHODS: We identified 21 patients who underwent surgery at least twice [male: 11, female: 10, median age: 44 years (31–66)]. Clinical data were available for 14/21 patients: 5/14 received a treatment between resections [4 radiotherapy, 1 radiotherapy followed by PCV chemotherapy]; median time from the first to the second surgery was 71.5 months (12–158). Whole genome DNA-methylation analysis was performed using Illumina's MethylationEPIC '850K' BeadChip. Results were evaluated using the Molecularneuropathology.org platform (version 3.1.5) and in R. RESULTS: Most samples were WHO grade 2 ODs [14, 10 and 1 tumours in first, second and third resection group, respectively]; WHO grade 3 was found in 6, 10 and 3 tumours in first, second and third resection, respectively; in 4 patients the tumour showed malignant progression from grade 2 to 3. Most ODs exhibited an IDH1 R132H mutation [17/21 patients]; in no cases was IDH1/2 mutation lost during progression. DNA methylation analysis was successfully performed in 41/45 cases [primary OD: 17, recurrent OD: 24] for a total of 18 matched pairs. 37 samples were assigned to the "IDH mutant glioma, subclass 1p/19q codeleted OD"; the remaining 4 were assigned to various other methylation classes but CNV (copy number variation) analysis confirmed the 1p19q codeletion in all samples. Recurrent tumours exhibited de novo loss of chromosome 4 in 3/24 cases (12.5%) and loss of chromosome 13 in 3/24 cases (12.5%). In unsupervised analysis of the 1000 most variable CpG sites, samples from the same patient clustered together. This indicates that the inter-tumour variability is greater than the intra-, temporal- or grading variability between tumours. There were no overt differences in DNA methylation levels between the primary and matched recurrent OD. However, lower genome wide DNA methylation levels were observed in tumours that dedifferentiated to grade 3 ODs compared to those of grade 2, indicating that DNA demethylation is associated to higher malignancy grade. CONCLUSION: DNA methylation analysis in a cohort of primary and recurrent oligodendrogliomas highlights the genomic and epi-genetic changes that are acquired at tumour progression. We are currently expanding the cohort and collecting/integrating the clinical data to better explore the evolution of recurrent ODs.